2023
DOI: 10.37022/wjcmpr.v5i5.294
|View full text |Cite
|
Sign up to set email alerts
|

Profiling of Clinical Dynamics of Type 2 Diabetes Mellitus in Patients: a Perspective Review

Aloysius Obinna Ikwuka,
Daniel Inioluwa Omoju,
Ousainou K Mahanera

Abstract: Type 2 diabetes mellitus (T2DM), also known as Non-Insulin Dependent Diabetes Mellitus (NIDDM) is one of the common metabolic disorders in the world. T2DM accounts for around 90% of all cases of diabetes mellitus, afflicting millions worldwide. It is a significant global health burden with a steadily increasing prevalence.  In T2DM, the response to insulin is diminished, and this is defined as insulin resistance. Risk factors for T2DM are diverse. Some are modifiable, and others are not. Modifiable risk factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Metabolic disorders e.g. Hypertension, Adiposity, Diabetes mellitus and Dyslipidemia collectively known as Metabolic Syndrome Diseases (MSDs) are diseases related to one another and have very high morbidity and mortality rates [15,16,18,33,35,52]. Results obtained from different researches have shown that hypertension, diabetes mellitus, adiposity and dyslipidemia, asymptomatic hyperuricemia, systemic immune inflammation activation and fibrogenesis, can lead to kidney damage [19,20,21,23,24,25,30,32,34,53,54,55,56,60], and can also affect the brain blood supply leading to neuronal damage.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolic disorders e.g. Hypertension, Adiposity, Diabetes mellitus and Dyslipidemia collectively known as Metabolic Syndrome Diseases (MSDs) are diseases related to one another and have very high morbidity and mortality rates [15,16,18,33,35,52]. Results obtained from different researches have shown that hypertension, diabetes mellitus, adiposity and dyslipidemia, asymptomatic hyperuricemia, systemic immune inflammation activation and fibrogenesis, can lead to kidney damage [19,20,21,23,24,25,30,32,34,53,54,55,56,60], and can also affect the brain blood supply leading to neuronal damage.…”
Section: Discussionmentioning
confidence: 99%